ANALISIS KETERAMPILAN GERAK LAY UP SHOOT DALAM PERMAINAN BOLA BASKET PADA PEMAIN TOGETHER BASKETBALL CLUB PAREPARE - Harliawan, Muhammad; Rahmi, Silatul (Dharmas Journal of Sport, 2024)
Basketball is a sport that requires mastery of basic techniques, where each player is required to be able to put the ball into the ring and protect his team's ring. This study aims to examine the level of lay up shoot skills in Together Basketball Club Parepare members. The research was conducted with a qualitative descriptive approach through a survey method, using test and measurement techniques. Researchers involved all 22 players from the club as research samples. The measuring instrument used was the lay up shoot skill test, with data analysis using descriptive percentages. The research findings describe the distribution of players' lay up shoot skills as follows: 4.5% (1 player) categorized as “very less” 27.3% (6 players) categorized as “less” 27.3% (6 players) categorized as “medium” 40.9% (9 players) categorized as “good” 0% (0 players) categorized as “excellent”. With an average score of 16.68 points which is in the moderate category, the study concluded that the lay up shoot skills of Together Basketball Club Parepare players are classified in the average or moderate category.